Uma proposta de ensino para a Geometria nos anos finais do Ensino Fundamental - Manoel, Wagner Aguilera (Universidade Federal de São Carlos, 2019)
The importance of teaching Geometry is a present theme in several researches in Mathematic Education (LORENZATO 1995, FONSECA et. al 2002; BRESSAN; BOGISIC; CREGO, 2010). These authors consider fundamental the presence of geometry in the school environment, be it for the importance of this subject in the culture and in the history of humanity, or be it through cognitives abilities that it develops, or, even through the fact that it is present in the student's day-to-day routine. Manoel (2014) has classified the contributions of teaching geometry in eleven axes of analyses (Curriculum, History, Other Areas of Knowledge, Nature, Quotidian, Affectivity, Problems Solving, Cognitive Abilities, Critical Thinking, Aesthetics Appreciation and Creativity) and has affirmed that these axes could be used as a method of Teaching Geometry. In the face of this problematic, the question that has emerged and has guided this research was: which are the contributions that the eleven axes can make it possible as methodology of teaching geometry for the second segment of middle school? The purpose of this research was to analyze the methodology of the 11 axes and to identify their contributions to the teaching of Mathematics in the situations of proposed learning. The methodology of research chosen was the qualitative of the naturalistic type, according to Fiorentini e Lorenzato (2006). The analyze, done with the help of five teachers from two schools from the city a Sorocaba-SP, it has used the register of the activities of these teachers. Through our analyze, it was possible to conclude that the eleven axes as a method of teaching Geometry help teachers in the preparation of their mathematic classes, choosing or creating activities or selecting the didactic material that present a greater amount of axes, contributing therefore for a preparation of more diversified, formative, critical, stimulating and creative classes, providing a better teaching of mathematic and an aid to other subjects such as Sciences, Physics and Arts.
A Geometry Teaching proposal for Middle School.
Keywords: Geometria; Ensino de geometria; Metodologia de ensino; Geometry; Teaching geometry; Methodology of teaching; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO